COMMUNICATION SATISFACTION AND EMPLOYEE COMMITMENT AMONG THE HYPERMARKET STAFF - Suhaini Muda; Vivekanthi Rethnakumar (INTERNATIONAL JOURNAL OF LAW, GOVERNMENT AND COMMUNICATION (IJLGC), 2024)
Communication plays an important role in many sectors and organisations to achieve their missions and goals. Effective communication in organisation is believed to contribute to job satisfaction among employees in the organisation. The main objective of this paper is to study the relationship between communication satisfaction dimensions and employee commitment among the staff at a Hypermarket in Melaka. Based on the quantitative approach, the data are collected through a survey conducted with 104 staff of the Hypermarket. The data collected in this study are analysed using SPSS application (version-26.0). Based on the multiple regression analysis, the studies reveal that the dimensions of communication satisfaction that influenced employee commitment the most are communication between employees. The results suggest some recommendations that can be implemented by the management of the hypermarket for improvement.